The Creative Thinking Process of Mathematics Education Students Based on the Wallas Thinking Stage in terms of Student Learning Barriers - Lukmanul Akhsani; Iwan Junaedi; Tri Sri Noor Asih (International Conference on Science, Education, and Technology, 2022)
Numerical methods are a course that studies mathematical problem solving in a systematic way using numbers. Students still have obstacles in learning numerical methods. These obstacles occur in the mental preparation of students in attending lectures, the lecture process carried out by lecturers and students' academic abilities. The purpose of this study is to describe the creative thinking process of students based on the Wallas stage. The method used is qualitative. respondents are students of prospective mathematics teachers. The data was obtained by testing the ability to think creatively. The test results were analyzed by looking at the creative thinking process according to Wallas, namely preparation, incubation, illumination, and verification. Furthermore, an analysis of test answers and in-depth interviews was carried out based on student learning barriers based on the obstacles faced. Interviews were conducted to students who have high, medium and low learning barriers. In general, students have obstacles in the creative thinking process, namely students only use the method of completion without understanding its meaning. This happens because students do not understand the concept well. As a result, students will not be able to solve problems from the lecturer properly if the form or illustration of the questions is changed.